Functionalization of chitosan via single electron transfer living radical polymerization in an ionic liquid and its antimicrobial activity. Issue 45 (26th August 2015) - Lin, Chunxiang; Liu, Danhui; Luo, Wei; Liu, Yifan; Zhu, Moshuqi; Li, Xiaojuan; Liu, Minghua
ABSTRACT In this work, single electron transfer living radical polymerization (SET‐LRP) was used to functionalize chitosan in a well‐controlled manner. The chitosan‐based macroinitiator was first synthesized and then initiated the SET‐LRP of methacryloyloxyethyl trimethylammonium chloride (DMC) in ionic liquid system, using Cu0/N, N, N′, N′, N′′‐pentamethyldiethylenetriamine as a catalyst. The grafting of PDMC brushes on chitosan was confirmed and analyzed by Fourier transform infrared spectroscopy and 1H nuclear magnetic resonance. Transmission electron microscopy reveals that the chitosan copolymer showed self‐assembled behavior in acetone. Surface properties of the copolymer have been investigated by environment scanning electron microscopy analysis. The linear relationship between the ln([M]0/[M]t) and time, the linear increase of number‐average molecular mass with conversion as well as the low polydispersity index of the polymer confirmed the "living/controlled" features of the polymerization of DMC through SET‐LRP. Finally, the chitosan copolymer demonstrates its potential antibacterial application, showing excellent inhibitive capability against Escherichia coli. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42754.